FORMATION AND DESTRUCTION OF ARCTIC THERMOHALINE STAIRCASES - Ainslie, Kristen (Monterey, CA; Naval Postgraduate School, 2021)
This study explores the dynamics of diffusive convection, which is realized in regions where cool and fresh water-masses rest on top of those that are warm and salty. This type of convection is often observed in the Arctic Ocean and is characterized by the development of fine-scale steps in vertical salinity and temperature profiles known as thermohaline staircases. The Arctic staircases control the rate of upward heat transfer from waters of Atlantic origin, thereby influencing the melting of sea-ice and the polar climate in general. This thesis aims to utilize numerical modeling to define conditions that are favorable or unfavorable for creating thermohaline staircases and provide an explanation as to why they are not constantly prevalent throughout the Arctic. In particular, the presented high-resolution simulations explore the role of vertical shear associated with internal waves that are ubiquitous in the World Ocean. While previous investigations suggested that that the vertical shear could adversely affect staircases, this effect has not been quantified and physical mechanisms at play are still poorly understood. The present study addresses these unresolved problems in the theory of double-diffusive convection, concurrently shedding light on the mechanics of heat transfer in high-latitude oceans. Approved for public release. distribution is unlimited Lieutenant, United States Navy